Shadow of Personal Fear? The Role of Personal and Altruistic Fear of Cyberharassment - Maher, Cooper A. (Crime & delinquency, 2024)
Fear of crime is a social problem that outpaces crime itself, particularly when fear is expressed altruistically for others. Despite this, few studies consider whether the correlates of fear are expressed differently across personal and altruistic contexts, and whether the correlates of these fears for cyberharassment differ across genders—a potentially gendered crime. Using data from two samples collected via randomized vignette design on Amazon’s MTurk (439; 419), logistic regression findings indicate that determinants of personal and altruistic fear of cyberharassment differ, and that altruistic fear is rooted in women’s personal fears. Findings indicate that altruistic fears of cyberharassment may stem from a “shadow of personal fear,” and indicate the need for further research examining this association across contexts.